Experiential learning in oral health education - Matina V Angelopoulou; Katerina Kavvadia (Wolters Kluwer Medknow Publications, 2018)
Experiential learning is an innovative learning method that knowledge is gained through experience. The aim of this paper was to review the application of experiential learning in health education and suggest an oral health education program using experiential learning. Experiential learning has been used in the past successfully in health education mostly in university curricula. In oral health education, its use is limited and without following a comprehensive structure. An experiential learning oral health education program, implemented in the classroom by a trained teacher, is proposed to be integrated in the school's curriculum. Initially, using brainstorming students express their opinions and feelings toward oral health. Then, students are allocated to working groups to develop oral health projects. The outcome of these projects is presented in the classroom to their peers through role playing, posters, songs, games, etc., Finally, a discussion is stimulated by the teacher to encourage children to express their feelings about oral health issues and thus experientially recognize the importance of oral health. Experiential learning has been effectively used in health education and can be a successful method for oral health education. For optimal results, a predetermined experiential method structure has to be followed.